Development of spray-dried powder hand sanitiser with prolonged effectivity - Večerková, Lucie; Mašková, Lucie; Knejzlík, Zdeněk; Kašpar, Ondřej; Tokárová, Viola (Scientific reports, 2024)
Since the outbreak of the COVID-19 pandemic, the use of hand sanitisers has become an inseparable part of our personal hygiene. However, the short-term effect and the need for frequent application are shortcomings that impair the overall protection. Another aspect is that repeated use of some products (typically alcohol-based) may cause skin irritation or eventually more severe health problems. This work proposes spray-drying as a suitable method for the preparation of swellable chitosan carriers, allowing for encapsulation and sustained release of antibacterial chlorhexidine digluconate as a model active substance. After application to hands, micron-sized particles preferentially accommodate space between epidermal ridges, protected against attrition. Thanks to their small size (d < 10 μm), particles are comfortable to carry since they are not recognisable by somatosensory receptors. The performance of formulations with various amounts of chlorhexidine and cross-linker was tested and compared with selected commercial disinfectants available on the Czech market (ethanol gel and alcoholic solution with chlorhexidine) against E. coli and S. epidermidis. The real-life performance was investigated with twelve volunteers performing various activities for up to 2 h. Finally, a replica of the human index finger with accurately captured micro-topology was proposed and compared with volunteers' fingers concerning the total amount of adhered and detached particles.
Keywords: dezinfekční prostředky na mytí rukou; pandemie; Pandemics; ruka; ethanol; Humans; prášky, zásypy, pudry; Escherichia coli; Chlorhexidine; Ethanol; lidé; chlorhexidin; Powders; Hand; Hand Sanitizers